PERFORMANCE ANALYSIS OF THE POLICE CIVIL SERVANTS’ UNIT IN MAINTAINING PUBLIC ORDER IN LANGKAT REGENCY (International Journal of Cultural and Social Science, 2026)
Public order is a fundamental aspect of community life that must be maintained to create a safe, comfortable, and orderly environment. The local government, through the Civil Service Police Unit (Satpol PP), has the primary responsibility for enforcing regional regulations and maintaining public order and public safety. This study examines the performance of the Civil Service Police Unit in maintaining public order in Langkat Regency and the factors that hinder its performance in maintaining public order in Langkat Regency. The research used is qualitative. Data collection techniques refer to the methods or means used to obtain the information needed for a study. This process is crucial to ensure that the collected data is valid, reliable, and in accordance with the research objectives. The results of the study indicate that, in general, the performance of the Langkat Regency Civil Service Police Unit is quite good, but not yet optimal. Factors hindering performance include limited human resources and operational infrastructure.